Chiral relay effects influence the facial selectivity of N-alkylated 5-phenylmorpholin-2-one enolates - Bull, S; Davies, S; Fox, D; Sellers, T (1998)
Alkylation studies on the enolate of N-methyl morpholinone 7 clearly reveal that the observed cis-selectivity is consistent with a chiral relay system operating to invert the stereochemical information of the auxiliary's C5 stereogenic centre.